A Project Report on Design and Development of Simulator for TT&C Receiver - KARTHIK B S, NAVEEN B M and SHESHADRINATH (2003)
INTERNAL GUIDE: PADMINI, MVJCE EXTERNAL GUIDE:RAGHAVENDRA, PRCD/SCG, ISRO SATELLITE CENTRE
Keywords: TT&C Receiver